Adenosine Deaminase 2 Deficiency (DADA2): A Crosstalk Between Innate and Adaptive Immunity - Signa, Sara; Bertoni, Arinna; Penco, Federica; Caorsi, Roberta; Cafaro, Alessia; Cangemi, Giuliana; Volpi, Stefano; Gattorno, Marco; Schena, Francesca (Frontiers in Immunology, 2022)
Deficiency of Adenosine deaminase 2 (DADA2) is a monogenic autoinflammatory disorder presenting with a broad spectrum of clinical manifestations, including immunodeficiency, vasculopathy and hematologic disease. Biallelic mutations in ADA2 gene have been associated with a decreased ADA2 activity, leading to reduction in deamination of adenosine to deoxyadenosine and subsequent accumulation of extracellular adenosine. In the early reports, the pivotal role of innate immunity in DADA2 pathogenic mechanism has been underlined, showing a skewed polarization from the M2 macrophage subtype to the proinflammatory M1 subtype, with an increased production of inflammatory cytokines such as TNF-α. Subsequently, a dysregulation of NETosis, triggered by the excess of extracellular Adenosine, has been implicated in the pathogenesis of DADA2. In the last few years, evidence is piling up that adaptive immunity is profoundly altered in DADA2 patients, encompassing both T and B branches, with a disrupted homeostasis in T-cell subsets and a B-cell skewing defect. Type I / type II IFN pathway upregulation has been proposed as a possible core signature in DADA2-T cells and monocytes but also an increased IFN-β secretion directly from endothelial cells has been described. In this review, we will explore thoroughly the latest understanding regarding DADA2 pathophysiological process, with a particular focus on dysregulation of both innate and adaptive immunity and their interacting role in the development of the disease.